Advances in the structural characterization and pharmacological activity of Salvia miltiorrhiza polysaccharides - Yang, Ke; Liu, Yi-Jun; Zhang, Jia-Ning; Chen, Ya-Jing; Yang, Jian; Xiao, Jun-Ping; Lin, Han-Bin; Yang, Hong-Jun (Frontiers in Chemistry, 2025)
BackgroundSalvia miltiorrhiza Bunge is the dried root and rhizome of Salvia miltiorrhiza Bunge, a labiatae plant. Salvia miltiorrhiza polysaccharide (SMP) is the main active component of Salvia miltiorrhiza Bunge. The extraction methods of SMP mainly include water extraction, ultrasonic extraction, enzyme extraction, microwave-assisted extraction and acid-base extraction. It is mainly composed of glucose, arabinose, rhamnose, galactose and other monosaccharides. SMP has a variety of biological activities, including immune regulation, anti-tum, anti-oxidation, myocardial protection, liver protection and so on.PurposeSalvia miltiorrhiza polysaccharide is widely used in nutraceuticals and pharmaceuticals, and has high research value. Natural polysaccharides are non-toxic, soluble in water, and have a wide range of biological activities, so they have broad research prospects.MethodsThe data was collected using different online resources including PubMed, Google Scholar, and Web of Science using keywords given below.ResultsIn the past decades, various reports have shown that the pharmacological activities of Salvia miltiorrhiza polysaccharides have good effects, and the side effects are small.ConclusionThis paper summarizes the extraction and purification methods, molecular weight, monosaccharide composition, glycosidic linkage, pharmacological activity, toxicity, product development, clinical research and other contents of Salvia miltiorrhiza polysaccharides in recent years, providing a theoretical basis for further study of Salvia miltiorrhiza polysaccharides.